Investigating the particle amount hanging in the air in the operating room during instrumented and non-instrumented neurosurgery operations - Arıkan, İnci and Şahin, Meryem Cansu and Kaya, İsmail and Cingöz, İlker Deniz and Aydın, Hasan and Bolu, Gözde (Journal of Surgery and Medicine, 2021)
Background/Aim: To improve patient safety and surgical results, it is highly significant to understand the factors which cause high particle matter (PM) levels in the air of the operating room. The objective of this study was to investigate the particle amounts hanging in the air in the operating room in instrumented and non-instrumented cases during Neurosurgery operations. Methods: This was an analytical study comparing PM amounts measured in 21 non-instrumented and 22 instrumented cases performed in Kütahya Evliya Çelebi Training and Research Hospital NRS operating room between March-May 2019. Five spots were identified in the operating room and measurements were performed at these spots by the same researcher during the operation. “Particles Plus 8306” particle measurement device was used for the measurements performed for 11 weeks. Also, detailed information such as operation duration, number of team members in the operating room and operating time of vaporizers per operation were registered on a form. Results: PM0.5 and PM1 amounts were higher in instrumented operations compared to non-instrumented operations. All PM amounts (except PM 0.5) measured in instrumented and non-instrumented operations decreased towards the end of the operation compared to the beginning (P=0.001, P=0.001, P=0.001, P=0.001 for all). Conclusions: PM smaller than one micron were detected more in instrumented operations compared to non-instrumented operations, and the amounts of these particles increased with the number of team members present. All PM amounts increased with operation durations, and all PM (except PM 0.5) amounts measured in non-instrumented and instrumented operations gradually decreased towards the end of the operation compared to the beginning. Regularly checking the air flow and restricting entry and exit in and out of the operating room are necessary.